Enhancing Secondary School Students’ Independent Learning, Conceptual Understanding, and Self-Efficacy of the Integration Concept through Photomath-Assisted Instruction - Onesme Niyibizi; Thierry Niyitegeka; Evode Nahimana; John Peter Kazinyirako; Jean Nepomuscene Singirankabo (Journal of Research in Education and Pedagogy, 2026)
This study assessed how well Photomath-assisted teaching strategies compared to conventional approaches in developing students’ capacity for independent study, improving their conceptual understanding of Integration Content, and boosting their self-efficacy in mathematics in Rwandan Senior Six. It carefully examined how Photomath’s effects varied depending on the student population and the learning environment. Using a non-equivalent control group pre-test–post-test design and a quantitative quasi-experimental methodology, 116 students who were purposefully chosen from public and private secondary schools, urban and rural, and from the PCM, PCB, and MCB academic tracks participated. The multivariate effects of the teaching strategy and its interactions with demographic factors were examined using multivariate analysis of variance (MANOVA). Additionally, diagnostic tests of assumptions (normality, homogeneity of variance-covariance, and multicollinearity) were performed before MANOVA, and all criteria were satisfied. Analyses were conducted using SPSS version 26 with α = 0.05. These methodological checks strengthen the validity of the findings. Regarding students’ independent study skills, conceptual understanding, and mathematics self-efficacy, statistically significant multivariate relationship effects were found between the instructional approach and variables like school location, gender, school type, and academic combination. This result implies that these demographic traits have an impact on Photomath’s effectiveness. By providing empirical evidence regarding Photomath’s varied impact within many different kinds of school contexts in Rwanda, this study fills a significant gap in the body of existing literature. It offers crucial information that educators and legislators may use to adjust technology integration tactics, improving fair and efficient mathematics instruction and reducing potential inequities.